ANALISIS STRATEGI GURU DALAM PEMBELAJARAN IPS DI SEKOLAH DASAR - Amalia, Ema Nur; Okta Preyera, Laisya; Mahera Shafitri, Novia; Ayu Saputri, Diska; Maharani, Aziza; Sofwan, Muhammad; Khoirunnisa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the strategies implemented by teachers in Social Studies (IPS) learning under the Merdeka Curriculum at the elementary school level. Using a qualitative approach with a case study design, data were collected through in-depth interviews, observations, and documentation. The research subject was a classroom teacher at SDN 111/I Muara Bulian who had implemented the Merdeka Curriculum in Social Studies instruction. The findings reveal eight main focus areas: the use of lecture, discussion, and assignment methods; the selection of learning media based on material needs; the use of ice-breaking and question-and-answer strategies; contextual approaches linking material to students' real-life experiences; individual and group learning; support for students experiencing difficulties; evaluation through formative, summative, and alternative assessments; and the optimization of learning resources. The study also highlights significant challenges in implementing assessment within the Merdeka Curriculum, particularly the need for clearer guidelines and more comprehensive training. Therefore, the successful implementation of the Merdeka Curriculum requires ongoing support from schools and the government, including pedagogical training, provision of learning media, and the development of applicable assessment policies to achieve the goal of meaningful and student-centered learning.